PROBLEMS OF RUSSIAN SCHOOL EDUCATION IN PISA CONTEXT - Zaia, Iosif; Manuylova, Ekaterina; Gevorkyan, Artur; Nesterov, Pavel; Gavrov, Sergei (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article based on the research which aim is to clear, how common teaching practices in Russian schools affecting the decline in the results of students when performing tasks of the Programme for International Student Assessment (PISA). The authors of the article try to understand why teachers so often prefer quite old training technologies. In the course of study these problems, members of research team conducted interviews and discussions with school teachers from the Moscow region who were trained in advanced training courses at the Academy of Public Administration. Intensive interaction with teachers helped the authors to draw a conclusion that the avoiding more effective contemporary training technologies is due to certain conditions in which the teacher works. Another conclusion made in the article: teachers fail in teaching students not because they do not have enough knowledge of modern technologies and techniques or because they underestimate the importance of developing critical thinking, anthropological imagination, knowledge of meta-subject connections, the skills to understand texts and work with heterogeneous information, but because they are not ready to accept the changing social role of the school.